Production-living-ecological functions measurement and spatio-temporal evolution of the coastal zone under the perspective of land-sea coordination: a case study of Liaoning Coastal Economic Belt - Ke, Lina; Wang, Lei; Wang, Quanming; Ren, Zhiyu; Lu, Yao; Yin, Shusheng; Zhao, Yu; Tan, Qin; Li, Yibo (Frontiers in Environmental Science, 2025)
The acceleration of urbanization and development of marine resources has led to the imbalance of land structure, which threatens the sustainable development of the human living environment. Exploring the spatial distribution patterns of land-sea and its spatio-temporal evolution characteristics is an important initiative to resolve conflicts and optimise the spatial structure of land-sea use. Taking the Liaoning Coastal Economic Belt as an example, this paper constructs a system to measure the value of Production-Living-Ecological Functions (PLEF) of the coastal zone and realizes the identification of Production-Living-Ecological Spaces (PLES) and the division of their combination patterns. At the same time, it analyses the spatio-temporal evolution of PLES using land use transfer matrix, center of gravity transfer and standard deviation ellipse models and explores the interaction mechanism of PLES from the perspective of land-sea coordination. The results show that: (1) The production and living spaces on land are concentrated near the coastline, and the ecological space is mainly distributed in the mountainous forest area. The sea is dominated by the production space, and the living and ecological spaces occupy a relatively small proportion. (2) While the land has significant multifunctionality, the sea has a single PLEF, with the production function dominating and accounting for more than 90%. (3) In the period 2005–2010, the frequency of mutual transformation of the different PLES was the highest. The increase is mainly in the living space on land and the production space at sea. (4) From 2005 to 2010, the patterns of land and sea PLES changed significantly, and from 2010 to 2020, they were relatively stable. This study analyses the spatial structure of land-sea from the perspective of spatial multifunctionality and proposes optimization schemes based on land-sea interactions, which can provide decision support for the identification and optimization of coastal zone space and sustainable development.